Plan-Do-Review-Share-Happy (Plandoresh) as strategy to develop independent learning of vocational school students - Aftoni Aftoni; I Wayan Susila; Any Sutiadiningsih; Muhammad Kris Yuan Hidayatulloh (Jurnal Pendidikan Vokasi, 2021)
When computers take over from routine tasks at work, some employees are involved in independent problem-solving tasks. The current learning system must encourage students to move to lower levels of thinking in order to become independent individuals. The purpose of this study was to test the validity of the Plan-Do-Review-Share-Happy (Plandoresh) strategy as an effort to develop independent learning for vocational school students. This study used a descriptive method, and the aim is to get the validity of the Plandoresh strategy steps with a random sample of 78 respondents. The results that 1.) The Plan step is valid with r count > r table of 0.849 > 0.227; 2.) The next steps are done valid with r count > r table of 0.873; 3.) The Review step is valid with r count > r table of 0.856; 4.) The Share step is valid with r count > r table of 0.868; and 5.) The happy step is valid with r count> r table  0.929. These results indicate that the steps of the Plandores strategy are valid to be applied in an effort to develop independent learning for vocational students.